Self‐supported Co, P‐codoped MnCO3 pyramid as an efficient Electrocatalyst for hydrogen evolution reaction. (27th August 2022) - Wang, Feng; Lv, Yinrong; Bai, Xueli; Zhang, Shengjian; Wang, Huifang; Li, Baoyi; Liu, Aifang; Zhang, Xiaoping
Summary: Polyhydride electrocatalysts integrated directly into metal substrates have attracted attention because they can provide high electrochemical specific surface area and excellent mechanical properties. In this work, through the classical hydrothermal method and subsequent phosphating procedure, we synthesized for the first time an electrocatalyst with a pyramid‐shaped MnCO3 as the main structure, P and Co as co‐doping elements, named Co, P‐MnCO3, and used it as hydrogen evolution reaction (HER). The experimental results show that the excellent catalytic activity in alkaline media, with current densities of 10 and 200 mA∙cm −2 at 61 mV and 158 mV and low overpotentials, which are better than P‐Co (108/234 mV) and P‐MnCO3 (175 mV/340 mV), etc. it has more electrochemically active sites, faster charge transfer rate and lower resistance. The excellent electrochemical properties benefit from the unique highly active binary Co, P‐MnCO3 pyramid brick sites shortened the ion transfer distance and optimized synergistic effect between the doped metal elements (Co, P between MnCO3 ), the porous connection between Co, P‐MnCO3 and the high conductivity substrate, increased the electron‐transfer efficiency between the substrate and material, accelerating the conversion of H + to H2 ; facilitated the release of bubbles and provided excellent mechanical properties for improved catalyst stability. This work provides a new idea for the synthesis of multi‐element electrocatalysts.